Métodos para caracterização de meios filtrantes contendo nanofibras - Salussoglia, Ana Isabela Pianowski (Universidade Federal de São Carlos, 2016)
It is necessary knowing the characteristics of the filter media and how they influence the filtration process to improve the filter media. With this, the aim of this study was to characterize the filter media containing nanofibers. The characterization of the filter was made by testing in experimental unit and through images generated by scanning electron microscopy analysis (SEM), which were treated with the softwares Gimp 2 and Image-Pro Plus 7.0 and electronic spreadsheet. In the experimental unit were conducted efficiency and permeability tests of the filter media with filtration area of 5.3 cm2. The efficiency was determined by the Particle Analyzer for Electric Mobility with face velocity of 4.7 cm/s. The particles were generated from a NaCl solution of 5 g/l. It was obtained the efficiency 74% considering the whole range of particle diameter. The permeability was obtained by Darcy equation it was possible to find the permeability of 2.5 10-08 cm2. The quality factor was calculated with efficiency and pressure drop and was 22.0 kPa-1. The SEM images were analyzed by two microscopes. The images generated by SEM - Magellan were greater number of pixels than images generated by SEM – FEG, because of this the images generated by SEM - Magellan were more accurate. The diameter of the nanofibers was evaluated by two methods. The automated method was more agile than the manual. Furthermore, it was made the evaluation of distribution models for the histograms of fiber diameters in the lognormal model was the best fit.
Keywords: Caracterização; Nanofibras; Microscopia eletrônica de varredura; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA